Kubachi - Derbent: cultural relationships in the Middle Ages - Mammaev, Misrihan Mammaevic (History, Archeology and Ethnography of the Caucasus, 2016)
On the basis of the data of written sources, archaeological materials, works of artistic craftwork and architectural onuments the author of the article highlights trade, economic, political and cultural ties between Zirikhgeran - Kubachi and Derbent in the Middle Ages. The author presents the list of articles of commerce between Derbent and the village of Kubachi, considers the problem of penetration of the Persian language, Zoroastrian features of funeral rites and Sufism from Derbent to Kubachi. The article covers ghazi campaigns from Derbent to Kubachi in the 12th century to plant Islam in this village and deals with some aspects of the influence of architecture of Derbent fortifications on architecture of Kubachidefence constructions of the 13th –14th centuries – round towers Akaila-kala, Kunakla-kala, and Kasumkalla-kala. It is noted that the ties in various spheres of economy and culture between Derbent and the village of Kubachi have preserved in modern and contemporary history.